Decarboxylation of lauric acids to long-chain alkenes via novel biochar-based photocatalysis under ambient conditions. (December 2022) - Fan, Yuwei; Qin, Xiaoli; Zhai, Yunbo; Huang, Zhongliang; Wu, Zijian; Tan, Mengjiao; Deng, Jiaqin; Zhu, Yun; Li, Hui
Abstract: Long-chain alkenes are an important class of energy chemicals and platform intermediates. In this work, the composite photocatalysts supported by Camellia shell biochar and Pt and TiO2 were successfully synthesized by the impregnation-calcination method, and the decarboxylation of lauric acid was achieved under ambient conditions. The composite photocatalysts were characterized and analyzed by Scanning electron microscopy (SEM), Transmission electron microscope (TEM), Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), UV–Vis diffuse reflectance spectra (UV–Vis DRS) and Energy band gap images. Compared with pure biochar, TiO2, and Pt/TiO2, the BC-PT-1 composite photocatalyst achieves the highest conversion rate of lauric acid under ambient conditions, reaching 84.47%. Surprisingly, the BC-PT-3 composite photocatalyst produced 1-decene from lauric acid conversion with up to 71.62% selectivity. The addition of biochar to the composite photocatalysts promoted light absorption beyond UV light and also improved the efficiency of electron-hole pair separation, facilitating the photocatalytic decarboxylation performance. After simple density functional theory (DFT) calculations, the generation of alkene is mainly due to the combination of the hole and the alkyl radical formed by the carboxylic acid. In conclusion, the composite photocatalysts in this study can be used for the photocatalytic decarboxylation of fatty acids to generate hydrocarbons, providing a new method for biomass upgrading. Graphical abstract: Image 1 Highlights: The novel composite photocatalysts were synthesized using Camellia shell biochar. Decarboxylation of lauric acid was achieved under 25 °C, ≤ 0.2 MPa H2 . The product 1-decene was generated for the participation of composite photocatalysts. Conversion of lauric acid reached 84.47% and selectivity of 1-decene reached 71.62%.